2022
DOI: 10.2147/opth.s374165
|View full text |Cite
|
Sign up to set email alerts
|

A Paradigm Shift in the Management Approaches of Proliferative Diabetic Retinopathy: Role of Anti-VEGF Therapy

Abstract: Diabetic retinopathy (DR) is considered one of the leading causes of vision loss globally. It principally causes upregulation of pro-angiogenic, proinflammatory, and vascular permeability factors such as vascular endothelial growth factor (VEGF), leading to neovascularisation. The advanced stage of DR or proliferative diabetic retinopathy (PDR) is of more concern, as it leads to vitreous haemorrhage and traction retinal detachment. Various risk factors associated with PDR include hyperglycemia, hypertension, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Since the late 20th, laser photocoagulation was used to destroy the part of the retina that lacks oxygen in order to avoid neovessel proliferation and to prevent hemorrhages in the vitreous, while vitrectomy was applied when blood extravasation affects visual acuity ( Oellers and Mahmoud, 2016 ; Zhang et al, 2023 ). In this respect, panretinal photocoagulation is still the main treatment for PDR, allowing the regression of retinal and papillary new vessels ( Raman et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the late 20th, laser photocoagulation was used to destroy the part of the retina that lacks oxygen in order to avoid neovessel proliferation and to prevent hemorrhages in the vitreous, while vitrectomy was applied when blood extravasation affects visual acuity ( Oellers and Mahmoud, 2016 ; Zhang et al, 2023 ). In this respect, panretinal photocoagulation is still the main treatment for PDR, allowing the regression of retinal and papillary new vessels ( Raman et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current therapeutic approaches for PDR mainly involve laser photocoagulation and intravitreal injection of anti-vascular endothelial growth factor (VEGF) drugs. However, these therapeutic modalities do not always effectively control the progression of PDR 5 . Moreover, studies have indicated that initiating intravitreal anti-VEGF medication increases the risk of acute thromboembolic events, particularly ischemic strokes 6 .…”
Section: Introductionmentioning
confidence: 99%
“…While angiogenesis is defective in cardiac microvessels in DM, it is pathologically enhanced in the retina. Overactive VEGF signaling and increased vascular permeability are involved in the pathogenesis of diabetic retinopathy [273]. Herein, miRNA expression profiling from STZ-mice informed on the downregulation of miR-200b.…”
Section: Mirnas In Pathogenesis and Potential Therapy Of Dm And Cvdmentioning
confidence: 99%